Improving the Mechanism of Budget Expenditures in the Healthcare Sector - Bakhrom Sotvoldievich Yuldashev (Zien Journals, 2023)
The article presents indicators of the effectiveness of the formation of goals and performance indicators of health care financing, depending on the function of financing budget expenditures, the introduction of new mechanisms for financing medical institutions
Keywords: healthcare financing; medical care; off-budget funds